Sustainable management of feedlot and agricultural runoff through bio-inspired bioreactor-constructed wetland configuration for high-quality reuse - de Oliveira Demarco, Jessica (Kansas State University, 2023)
Pollution from animal wastes is a threat to water resources. Animal agriculture generates substantial amounts of manure, typically collected and stored in wastewater lagoons on farms. Insufficient treatment and disposal of animal manure results in potential runoff and leaching of waste into surface and groundwater, causing environmental damage (e.g., algal blooms and fish kills) and contaminating drinking water in many rural areas. As global concerns regarding water security and environmental pollution continue to rise, new economic, sustainable solutions for runoff management and wastewater treatment are crucial. The ultimate goal of this research is to assess the efficiency of an innovative configuration of anaerobic membrane bioreactor (AnMBR) technology and constructed wetlands (CWs) systems to provide a sustainable, resilient management system for agricultural wastewaters. Additionally, this dissertation explores the broader issue within ecological engineering by evaluating the impact of using different terms on the field’s advancement and communication through a bibliometric analysis. Moreover, this study investigated the capacity of eastern red cedar biochar to decrease the concentrations of target antibiotics that have been extensively used in the swine industry, such as tetracycline, oxytetracycline, chlortetracycline, sulfadiazine, and sulfamethazine. Finally, preliminary CW designs were evaluated using HYDRUS CW2D to better assess system variability and function. A bibliometric analysis was performed using the bibliometrix package in RStudio on environmental engineering, ecological engineering, nature-based solutions, engineering with nature, constructed wetlands, green engineering, and ecological systems. The results showed that these terms developed over different periods with a recent increase in the scientific literature. Scientific production in environmental engineering and ecological systems started in the early 1960s, gaining force in the 1990s and reaching a peak in 2020 with 4779 and 1398 publications, respectively. The growth of ecological engineering is stagnant with first publications in 1971 and reaching a peak in 2018 with 145 publications. Nature-based solutions is becoming more popular with the first publication in 2009 and thriving in 2020 with 323 publications. Engineering with nature, on the other hand, was dated in 2001, reaching a peak of 5 in 2018. Constructed wetlands and green engineering started in 1985 and 1991, reaching a peak in 2020 with 818 and 55 publications, respectively. The term constructed wetlands was chosen as part of the ecological engineering field. However, the most substantial connection appears to be with environmental engineering. Environmental engineering remains the predominant area, with nature-based solutions gaining popularity instead of ecological engineering. To remove antibiotics from swine wastewater, eastern red cedar biochar was produced by pyrolysis from eastern red cedar at 450 ºC. The sorption tests were performed by mixing biochar and a solution containing each antibiotic in 100, 300, 600, and 900 [mu]g L⁻¹ concentrations. The results indicate that red cedar biochar was able to effectively remove up to 99.93% of tetracycline, 96.23% of oxytetracycline, 98.28% of chlortetracycline, 76.4% of sulfadiazine, and 78.6% of sulfamethazine at the lowest concentrations. The removal efficiency at higher concentrations declined up to 83.52%, 47.23%, 64.16%, 69.8%, and 58.4% for tetracycline, oxytetracycline, chlortetracycline, sulfadiazine, and sulfamethazine, respectively. The adsorption capacity and mechanisms were significantly influenced by each antibiotic's chemical properties and the biochar's surface properties. Overall, the results highlighted the potential utilization of eastern red cedar biochar as filter media in CWs systems. Numerical simulations were conducted to assess the capacity of CWs to remove nutrients from AnMBR permeate varying NH₄⁺, P, and chemical oxygen demand (COD) concentrations and temperature conditions (10, 20, 30, and 40 ºC). The simulations were conducted using HYDRUS software with the CW2D module. The results supported the assumption that the given CWs design can be an efficient polishing step for AnMBR permeate, removing more than 90% of NH₄⁺ and P, further confirmed with experimental measurements. The effectiveness of this design relies on the natural processes for nutrient removal that can be optimized by altering nutrient and COD loading rates from the AnMBR system. When AnMBR systems face unexpected failures or technical issues, the integration of CWs provides a reliable contingency plan, ensuring a practical and resilient wastewater treatment process. The findings from this research offer significant promise for developing cost-effective and environmentally friendly solutions for the treatment and reuse of agricultural runoff, contributing to the broader goals of sustainable water management and agricultural practices.
Keywords: Wastewater treatment; Anaerobic membrane bioreactor; Swine wastewater; Pollutant removal; Constructed wetland systems